Optimal fluid management strategies in patients with heart failure: a systematic review and meta-analysis of randomized controlled trials - Adamu, Umar G.; Muponda, Blessing; Tsabedze, Nqoba (Frontiers in Cardiovascular Medicine, 2025)
BackgroundFluid restriction is frequently recommended in heart failure (HF) management to prevent volume overload and improve clinical outcomes. However, the evidence supporting this practice remains limited. This meta-analysis aimed to evaluate the impact of fluid restriction vs. liberal fluid intake on clinical and patient-centered outcomes in individuals with HF.MethodsA systematic search of PubMed, Embase, Cochrane Library, and ClinicalTrials.gov was conducted through April 27, 2025, to identify randomized controlled trials (RCTs) comparing restrictive and liberal fluid strategies in HF. Pooled risk ratios (RRs) for binary outcomes and weighted mean differences (WMDs) for continuous outcomes with 95% confidence intervals (CIs) were calculated using a random-effects model.ResultsFour RCTs with a total of 747 patients were included, of whom 378 (50.6%) were randomized to liberal fluid intake. There were no significant differences between groups regarding all-cause mortality (RR: 1.71; 95% CI: 0.37–3.72; p = 0.27), HF rehospitalization (RR: 0.71; 95% CI: 0.46–1.10; p = 0.13) or thirst (WMD: 4.78; 95% CI: −6.72 to −16.28; p = 0.42). Patients in the fluid restriction group had significantly lower fluid intake (WMD: −361.84 mL/day; 95% CI: −552.89 to −170.78; p < 0.001), lower Kansas City Cardiomyopathy Questionnaire (KCCQ) Clinical summary score (WMD: −361.84; 95% CI: −552.89 to −170.78; P < 0.001), and lower adherence (WMD: 16.47; 95% CI: 6.45–26.50; p = 0.001). No significant differences were observed between groups in terms of acute kidney injury, weight loss, or patient-reported quality of life.ConclusionsIn this meta-analysis, fluid restriction significantly reduced total fluid intake but did not improve clinical outcomes in patients with HF. Adherence and KCCQ clinical summary scores were higher with liberal fluid intake. These findings support an individualized approach to fluid management in patients with HF.Systematic Review RegistrationPROSPERO CRD420251048914.